American Diplomacy / A History - Ferrell Robert H (W.W. Norton & Company, 1975)
Preface, The Tradition and the Men and the Mechanisms, The American Revolution, The Commerce of a New Nation, Neutrality and Quasi War, The Louisiana Purchase, The War of 1812, Era of Good Feelings, Manifest Destiny, The Northeast and Northwest Boundaries, Expansive Projects, Civil War, The Republic at Peace, The New Manifest Destiny, New Opportunities, The War with Spain, The Far East - 1899-1921, Colossus of the North, World Power, Nutrality - 1914-1917, War and Peace, The Twenties, The Great Depression, To Pearl Harbor - 1939-1941, The Second World War, Europe - 1945-1950, Europe in Recent Years, The Two Chinas, Japan and the Korean War and Southeast Asia, The Middle East and Africa, Good Neighbor in Latin America, Vietnam, The Diplomatic Revolution: The New Weapons and Diplomacy, Prospect, Index.